81 Can Simulation-Based Training be Used to Teach Geriatric Medicine?. (6th February 2020) - Oates, R; Lettal, K; Allen, N; Deivasikamani, G
Abstract: Introduction: Health Education England (HEE) and the Joint Royal Colleges of Physicians Training Boards recognise the importance of simulation-based training especially for Core Medical Trainees in improving patient outcomes and enhancing learning (Enhancing UK Core Medical Training through Simulation based training, Health Education England 2016). Research also suggests simulation training can be used to address a wide variety of medical curricula agenda from emergency presentations to breaking bad news (Beaubien 2004, Quality & Safety in healthcare). HEE suggests simulation training can be used to develop understanding but also communication skills and awareness of human factors and are focusing on developing a national strategy. Geriatric Medicine is complex and trainees are expected to be competent in managing elderly patients in a variety of presentations. Our aim was to ascertain the confidence levels of CMT doctors managing elderly patients and whether simulation-based teaching is effective for geriatric teaching. Methods: Three scenarios addressing common geriatric conditions were developed by a Geriatric Medicine Registrar and overseen by Geriatric Consultant. Scenarios including delirium secondary to sepsis, Opiate toxicity secondary to acute kidney injury (complicated by addressing dementia and risk of self-harm) and identifying and demonstrating appropriate palliative approaches to a catastrophic subdural haemorrhage. Trainees were given a brief summary of a case and asked to review and manage the 'patient'. A geriatric registrar alongside two CMT doctors designed a pre and post confidence questionnaire using Likert scales and free text boxes to explore respondents' views. Results: 100% of trainees found the simulation training useful and would recommend the sessions. 100% of trainees stated preference for simulation-based teaching opposed to lecture and work based assessments. Confidence increased across all three scenarios post simulation. 70% of trainees stated they felt confident to manage delirium with sepsis pre-simulation, this increased to 91% post simulation. Trainees commented 'feel confident to manage sepsis but not complicated by delirium or AKI' and 'prefer simulation to lectures' Conclusions: CMT doctors enjoy and find simulation training in geriatric medicine useful and show preponderance to this. Simulation training can be used to expose trainees to real life complex geriatric medicine scenarios in a safe environment. This programme will be developed to encompass additional medical scenarios and also to be delivered to foundation year doctors.